Raman spectroscopy and electronic microscopy structural studies of Caucasian and Afro human hair. Issue 5 (May 2019) - dos Santos, Jordana Dias; Edwards, Howell G.M.; de Oliveira, Luiz Fernando Cappa
Abstract: Human hair fibre is subjected to various structural modifications due to the application of chemicals such as dyes, shampoos and bleaches and/or physical procedures such as heating, and often more than one procedure is performed on the same hair. The present work aims to analyze the changes incurred in hair samples of two ethnic groups, namely Caucasian and Afro, before and after different treatments such as thermal, bleaching and straightening. In addition to observing the damage caused by each treatment separately, the study of samples that received all three treatments was carried out. For molecular structural characterization, the Raman vibrational spectroscopic technique was used and scanning electron microscopy (SEM) was used for morphological analysis of the hair fibres. This investigation has shown, through vibrational spectroscopy, that several important bonds have been modified, such as the S-S, C-S, C-C and S-O bonds as well as the secondary structures of proteins that have indergone changes in their conformation as a result of the treatment. Hair from the two ethnic groups showed small differences in relation to each applied treatment. Excessive heat generated a higher rate of Raman spectral band intensity changes when compared to the other treatments and it was observed that the action of several treatments on the same hair fibres resulted in even more pronounced structural changes. Finally, scanning electron microscopy showed that each treatment caused a different morphological deformation pattern on the capillary surface of the human hair.